Biopolymer nanoparticles designed for polyunsaturated fatty acid vehiculization: Protein-polysaccharide ratio study - Perez, Adrián Alejandro (2015)
Information about the design of biopolymer nanoparticles (BNPs) for polyunsaturated fatty acid (PUFA) vehiculization is provided. Linoleic acid (LA) was used as a model PUFA. The binding ability of LA to β-lactoglobulin (BLG) was applied for obtaining BLG-LA complexes. BLG-LA complex formation was monitored by fluorimetry and it was observed that a moderate heat treatment (60 °C, 10 min) enhanced BLG-LA complexation. Obtaining BNPs involved the electrostatic deposition of high methoxyl pectin (HMP) onto the BLG-LA complex surface. The phase behavior of biopolymer systems was discussed at different Prot:HMP ratio (RProt:HMP, wt.%) levels (1:1-6:1). Absorbance at 600 nm, particle size, and ζ potential were analyzed at pH 4.0. At 1:1-2:1 RProt:HMP, BNPs showed appreciable turbidity, a nanometric diameter (337-364 nm), and a negative ζ potential. Finally, intrinsic and extrinsic fluorimetry was used for examining the HMP protective role at the LA binding site. At 2:1 RProt:HMP, HMP cover could promote significant LA protection in BNPs.